IBM Lotus Quickr 8.5 for Domino administration : ensure effective and efficient team collaboration by building a solid social infrastructure with IBM Lotus Quickr 8.5 /: ensure effective and efficient team collaboration by building a solid social infrastructure with IBM Lotus Quickr 8.5. (2011) - Unknown
No abstract available